1993
DOI: 10.1148/radiology.186.3.8430176
|View full text |Cite
|
Sign up to set email alerts
|

Renal oncocytoma and carcinoma: failure of differentiation with CT.

Abstract: The authors studied the hypothesis that oncocytoma and adenocarcinoma of the kidney can be differentiated with computed tomographic (CT) criteria and that differences would become more apparent as tumors enlarged. On contrast material-enhanced scans, homogeneous attenuation throughout the tumor and a central, sharply marginated, stellate area of low attenuation were considered predictors of oncocytoma. Any area of decreased attenuation in the tumor except for a stellate, central area was used as a predictor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(60 citation statements)
references
References 0 publications
2
51
1
6
Order By: Relevance
“…Results from a meta-analysis across 1711 participants and 21 studies have indicated that expression of CK7 is a major immunohistochemical marker for differentiating RCC from oncocytoma [48]. Oncocytomas enhance avidly and relatively homogeneously during the corticomedullary phase without signs of necrosis or hemorrhage, and may have a low attenuating central stellate scar on CT [59][60][61][62]. On MRI, oncocytomas are typically round well-defined masses with hypointense T1 signal and hyperintense T2 signal relative to renal cortex [63] (Fig.…”
Section: Composite Papillary Renal Cell Carcinoma and Oncocytomamentioning
confidence: 99%
“…Results from a meta-analysis across 1711 participants and 21 studies have indicated that expression of CK7 is a major immunohistochemical marker for differentiating RCC from oncocytoma [48]. Oncocytomas enhance avidly and relatively homogeneously during the corticomedullary phase without signs of necrosis or hemorrhage, and may have a low attenuating central stellate scar on CT [59][60][61][62]. On MRI, oncocytomas are typically round well-defined masses with hypointense T1 signal and hyperintense T2 signal relative to renal cortex [63] (Fig.…”
Section: Composite Papillary Renal Cell Carcinoma and Oncocytomamentioning
confidence: 99%
“…It is important to mindful that even very large lesions may be benign, and that if possible, organ sparing surgery should be a consideration. [48,49,50,51]. Familial renal oncocytomatosis is relatively uncommon, but also has been noted.…”
Section: Renal Oncocytomamentioning
confidence: 99%
“…[149] Renal oncocytoma is typically described to be a hypervascular, homogeneous mass that may contain a central stellate scar on computerized tomography (CT). However, extended experience has proved these findings to be unreliable and of poor predictive value [48,49,50,51]. However, oncocytomas also appear to be quite vascular, and have a contrast uptake and drainage curve different from that of clear cell renal cell carcinoma.…”
Section: Computerized Tomography and Differentiation Of Renal Massesmentioning
confidence: 99%
“…En nuestra serie este valor es de 9,9% (2/22) si hablamos de sospecha de OR, y de 22,73% (5/22) si lo hacemos de tumor benigno. Además en RCC menores de 3 cm la posibilidad de error es mayor en los tumores de menor tamaño, encontrándose en la serie de Davidson que hasta un 42% de CCR menores de 3 cm se diagnosticaron como OR usando los criterios de homogeneidad o presencia de cicatriz central 27 .…”
Section: Discusionunclassified